2021
DOI: 10.1177/0300060521996517
|View full text |Cite
|
Sign up to set email alerts
|

Otological manifestation of temporomandibular joint disorder in Ekiti, a sub-Saharan African country

Abstract: Objective To determine the prevalence, sociodemographic features, and clinical presentation of temporomandibular joint disorder in otorhinolaryngological practice. Methods This prospective hospital-based study involved patients diagnosed with temporomandibular joint disorder in our institution’s ear, nose, and throat department. Data for this study were obtained from the patients using pretested interviewer-assisted questionnaires. Results The prevalence of temporomandibular joint disorder in this study was 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…During the penultimate step of the evaluation of the 78 studies, it was noted that only 2 studies were from the African population [ 34 , 35 ], and 1 study was from the Australian population [ 36 ]. Because single studies for Australia and Africa were found, conducting a meta-analysis for these continents was impossible.…”
Section: Methodsmentioning
confidence: 99%
“…During the penultimate step of the evaluation of the 78 studies, it was noted that only 2 studies were from the African population [ 34 , 35 ], and 1 study was from the Australian population [ 36 ]. Because single studies for Australia and Africa were found, conducting a meta-analysis for these continents was impossible.…”
Section: Methodsmentioning
confidence: 99%